Psalm 118 (117 lxx) in Luke-Acts: Application of a 'New Exodus Motif' - Kwon, Hyuk J. (Verbum et ecclesia, 2009)
This contribution explores the presence of Psalm 118 (117 LXX) in Luke-Acts. The Wirkungsgeschichte of Psalm 118 will be traced by means of a twofold approach: from a traditional-historical and a hermeneutical angle with regard to the reception history of Psalm 118. Firstly, in terms of a traditional-historical, otherwise known as a diachronic, approach, the background of Psalm 118 and evidence of the use and application of Psalm 118 in the tradition (namely in the ancient Jewish materials, such as the Dead Sea Scrolls, the Targums, and Rabbinics, and the New Testament books of Mark, Matthew, Luke, Acts, John, Romans, 2 Corinthians, Ephesians, 1 Peter, Hebrews, Revelation, as well as in terms of Church Fathers 1 Clement and Barnabas and the Apocryphon Thomas) will be discussed. Secondly, on the hermeneutical level, otherwise known as the synchronic approach, the function and interpretation of the quotations of Psalm 118 in its new context of Luke-Acts will be examined. In terms of the latter approach, attention will be paid to investigating a possible underlying ‘New Exodus Motif’.